2016
DOI: 10.1051/matecconf/20168015011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a composite ring rolling process by FEM and experiment

Abstract: Abstract. Roll bonding is a well-known process to produce composite sheet metals. Transferring this principle to ring rolling would allow to produce seamless radial composite rings, which combine the advantages of different material properties. This process is studied, both experimentally and using FEM-simulation. For the FEM an explicit model is applied including the kinematic control algorithms of the radial-axial ring rolling machine. In the used model the occurrence of unexpected asymmetrical joints can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Gheisari et al [7] conducted a 3D-FE analysis in hot forming conditions, obtaining an optimization guide of process parameters and quality control. Seitz et al [8] investigated the ring rolling process for realizing seamless composite rings to maximize the mechanical properties. Considering the optimization of final quality, Anjami et al [9] have demonstrated that tool size influences strain and temperature distribution, finding the optimal configuration and reducing the fishtail effect.…”
Section: /1mentioning
confidence: 99%
See 1 more Smart Citation
“…Gheisari et al [7] conducted a 3D-FE analysis in hot forming conditions, obtaining an optimization guide of process parameters and quality control. Seitz et al [8] investigated the ring rolling process for realizing seamless composite rings to maximize the mechanical properties. Considering the optimization of final quality, Anjami et al [9] have demonstrated that tool size influences strain and temperature distribution, finding the optimal configuration and reducing the fishtail effect.…”
Section: /1mentioning
confidence: 99%
“…Considering the optimization of final quality, Anjami et al [9] have demonstrated that tool size influences strain and temperature distribution, finding the optimal configuration and reducing the fishtail effect. ation of the ring rolling pr olling process [6,8,12]. ocess [6,8,12].…”
Section: /1mentioning
confidence: 99%